Features of Teacher’s Synchretic Activity in the Conditions of Modern Higher Education - Drozdova, Irina (2021)
Effective feedback is an art that every leading teacher must improve. The student, who receives excellent feedback during the lesson, walks out of the door feeling confident and motivated for further improving. A student who receives poor feedback will feel the opposite. The feedback should be defined like "great work" with the meaning not only about how to correct the mistakes of students so that they can study in the future without undermining their confidence but also about the modern teacher’s role in educational process. The article has been raised the issue of the specific features of the teaching activities, the essence of the concept of "syncretic activity of the teacher "is reveald, in particular the concept of "role functions" is clarified, approaches to interpreting the features of the role functions of a teacher are considered. The main instructions of the teacher which provide the identification of teacher’s new qualities in the conditions of modern higher school have been highlighted. The teacher is entrusted with such functions as coordination of educational activities, adjustment of the content of education, counseling, etc. The solution of this problem in terms of personal and professional growth of the teacher has been proposed, which allows to improve the teaching process in higher education. The author's understanding of the main roles of the teacher in higher school has been outlined, the attention on urgent tasks, the features of the role functions of a teacher as syncretic multifunctional interaction between the teacher and the student on preparation of experts for information society has been emphasized. The sequence and priority of the teacher's roles in the syncretic activity in the teaching process have been revealed. The psychological structure of the teacher’s syncretic activity has been clarified from the point of view of the requirements for teacher’s personality with an explanation of the set of skills that the teacher of a higher education institution should have. The professional skills of the teacher in relation to the peculiarities of his or her activity, which are shown in various types of the teacher’s role functions in accordance with the situation and professional tasks of teaching have been analyzed. It has been shown that the transformation of educational activities and role functions of a modern teacher of higher education testifies to constant changes in his personal and professional growth, which also affects the development of the personality of a student - a future professional - in the process of his training.